Comparação do efeito do período de recuperação da fadiga muscular no andar entre adultos jovens e idosos - Beretta, Stephannie Spiandor [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The effects of muscle fatigue on motor control of the gait are age-dependent. Also, it is known that the strength and the quality of muscle contraction decline with the advance of the age, impaired the motor control of gait and daily activities. However, studies about the effects of the muscle fatigue recovery time on gait in old adults are scarce. The aim of the study was to compare the effects of different recovery periods (5, 10 and 20 minutes) after muscle fatigue of quadriceps in gait among young and old adults. Forty young adults with age between 20 and 40 years old and forty older adults with age above sixty years old were enrolled in the study. Participants performed the following tasks: i) walking task: participants performed 3 trials in selfselected velocity in a 8 meters long pathway; ii) maximal voluntary contraction protocol: it was performed in a leg press machine. They performed 2 trials for each period; iii) fatigue induction protocol: the quadriceps fatigue was induced by the sit-tostand task until voluntary exhaustion; iv) participants repeated the first and the second items immediately after the fatigue induction and after 5, 10 and 20 minutes of rest. In the walking task was analyzed the central stride of each participant in each trial. It was analyzed the kinematic (stride length, step width, double support percentage, stride velocity and stride duration), kinetics (anteroposterior and vertical braking and propulsive impulses) and electromyographic (RMS and peak of electromyographic activity of the medial and lateral vastus, biceps femoral, medial and lateral gastrocnemius and tibialis anterior). Data were compared by MANOVAs two-way with factor group (young adults X older adults) and recovery period (before muscle fatigue X after muscle fatigue X 5 minute recovery X 10 minutes recovery X 20 minutes recovery) with repeated measures to the last factor. In general, the results show that muscle fatigue changes the...

Efeitos da fadiga muscular no controle motor do andar são dependentes da idade. Ainda, é conhecido que a força e qualidade de contração muscular declinam de acordo com o avanço da idade, prejudicando o controle do andar e realização das atividades diárias. No entanto, pouco é conhecido sobre o efeito do tempo de recuperação da fadiga muscular no andar de idosos. Sendo assim, o objetivo foi comparar o efeito de diferentes tempos de recuperação (5, 10 e 20 minutos) da fadiga muscular do quadríceps no andar entre adultos jovens e idosos. Participaram do estudo 40 adultos jovens entre 20 a 40 anos e 40 idosos acima de 60 anos. Os participantes realizaram as seguintes tarefas: i) andar em ambiente regular: sendo realizadas 3 tentativa em velocidade preferida caminhando 8 metros em cada tentativa; ii) protocolo de contração voluntária máxima: realizado no aparelho de Leg Press, sendo duas tentativas para cada momento de realização; iii) protocolo de indução à fadiga: induzida pela tarefa de sentar e levantar até a exaustão voluntária do participante; iv) repetição dos dois primeiros itens após a indução à fadiga e após 5, 10 e 20 minutos de descanso. Na tarefa de andar foi analisado a passada central de cada participante em cada tentativa. Foram analisados os parâmetros cinemáticos (comprimento, velocidade e duração da passada, largura do passo, porcentagem de duplo suporte), cinéticos (impulso vertical e horizontal anteroposterior de frenagem e de propulsão) e eletromiográficos (RMS e pico da atividade eletromiográfica dos músculos vasto lateral e medial, bíceps femoral, gastrocnêmio lateral e medial e tibial anterior). Os dados foram comparados através MANOVAs two-way com fator para grupo (adultos jovens x idosos) e período de recuperação (antes da fadiga muscular X após fadiga X 5 minutos de recuperação X 10 minutos de recuperação X 20 minutos de recuperação) com medidas repetidas para o último...
Keywords: Educação fisica para idosos; Fadiga; Aptidão física; Estabilidade; Locomoção humana; Capacidade motora